Strengths and weaknesses of the organization and operation of Inspection of Education - Secadura Navarro, Tomás (Avances en Supervisión Educativa, 2014)
The study was performed by the technique of Legislative Research (hemerographic), focused on the revision of the existing legal corpus in the Spanish State on the action of the Education Inspectorate (work plans), to assess the strengths and weaknesses in your organization and operation, since the dimensions of the Inspection: structure, planning, action- instrumentation and approach-purpose.The identified weaknesses prove the suitability of a structural review of the Inspection (model change); plus other factors also for the urgency of adjustment are analyzed because they are causing the loss of half of Inspection: proximity and connection between the educational authorities and schools themselves; the growing autonomy of schools and the enhancement of the role of the Directors; the application of information technologies and communication management center networks; and external evaluations.We conclude that modern Inspection needs a new "macro" approach, and around it should swing the other strategic changes, the new expectation would assume that the purpose of the inspection is the educational system and its improvement.
Keywords: education inspectorate; strengths and weaknesses of the inspectorate; autonomy of schools; school management; action plans; inspection model; educational system